2011
DOI: 10.12968/bjom.2011.19.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of birth in a stand-alone centre compared to other options

Abstract: Promoting choice is central to current NHS policy. In seeking to better understand the choices women make, this study aimed to identify if women would choose to give birth in a stand-alone birth centre, and the factors influencing this choice. A survey approach was adopted, and 121 responses were obtained (a response rate of 53%). The majority (n = 76, 62.8%) of responders would choose to have their baby in a stand-alone birth centre. The provision of a homely environment, opportunities for a natural birth, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“… February to March 1996 Study focuses on service attributes preferred antenatally vs. postnatally. Rogers (2011) [ 24 ] This study was conducted to evaluate the viability of converting an AMU in outer London to an FMU following the planned closure of the OU in the hospital. The study focused on whether users of the existing AMU would choose the new FMU or would look for an alternative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… February to March 1996 Study focuses on service attributes preferred antenatally vs. postnatally. Rogers (2011) [ 24 ] This study was conducted to evaluate the viability of converting an AMU in outer London to an FMU following the planned closure of the OU in the hospital. The study focused on whether users of the existing AMU would choose the new FMU or would look for an alternative.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies used discrete choice or other experimental stated preference methods [ 15 , 16 , 18 20 ]; five asked women to rate the aspects of maternity services that were important to them [ 15 , 16 , 21 23 ]. One study reported women’s reasons for choosing a specific unit or setting [ 24 ]; and one study asked women to state what factors had affected their booking decision [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A third group of studies has explored the importance women place on a diverse range of attributes (or having information about a diverse range of attributes ) when choosing a particular birth setting. These studies represent those most useful for inferring women's information priorities and broadly suggest that women value information about qualities of the birth environment (e.g., homeliness) , support for patient autonomy or involvement in decisions , availability of specialty services in the event of complications , access to specific birthing options or provider support , and other women's recommendations of the birth setting . Notwithstanding, these studies have focused on attributes that tend to vary between birth settings of a similar type, which means they either did not assess the importance of attributes that are universal across settings but vary between models of care (such as the birth setting itself), or attributes that may vary across different models of care available at a particular type of birth setting (such as choice of provider and continuity of care).…”
Section: Models Of Maternity Care In Queensland As Presented In Partmentioning
confidence: 99%